(S)-(+)-N-Benzylidene-1-(1-naphthyl)ethylamine - Bernès, Sylvain (International Union of Crystallography, 2011)
In the title chiral aldimine, C19H17N, the azomethine group is not fully conjugated with the phenyl substituent: the dihedral angle between phenyl and C*—N=C mean planes is ϕ3 = 23.0 (2)°. Compared with the earlier DFT-B3LYP/6–31 G(d) computations from the literature, the C=N—C*—C(naphthyl) torsion angle, found at ϕ2 = −118.0 (2)° in the X-ray structure, does not match the angle calculated for the potential minimum energy at ϕ2 = 0°. However, this angle is close to the second potential energy minimum at ϕ2 = −120° which is ca. 8.5 kJ mol−1 above the global energy minimum. Thus, the reported X-ray structure corresponds to the second most likely (according to DFT) conformer, allowing the existence of other polymorphs to be anticipated.